An efficient model for the TIG‐dressing process numerical simulation. Issue 3 (7th February 2019) - Ferro, Paolo; Romanin, Luca
Abstract: TIG‐dressing is a post‐welding operation consisting in the remelting of the weld toe region aimed to promote a reduction of the stress concentration effect in that zone by an induced smoother transition between the plate and the weld crown. Furthermore, a residual stress redistribution is expected that contributes to enhance the fatigue strength of the welded joint. Unfortunately, these effects are very difficult to be quantified by numerical simulation since a highly coupled thermo‐fluid‐mechanical analysis is required. In this scenario, a simplified numerical model of the TIG‐dressing process is proposed that overcomes the necessity to use a coupled thermo‐fluid‐mechanical analysis.